DYTOCIA DUE TO MONOCEPHALUS TETRABRACHIUS TETRAPUS FETAL MONSTER IN EWE: DYTOCIA MONOCEPHALUS TETRABRACHIUS TETRAPUS IN EWE - Bhat, Ghulam Rasool; Yousuf, Nahida; Singh, Pawan Preet; Gugjoo, Mudasir Bashir; Khatun, Arjuma; Lone, Farooz Ahmad (The Indian Journal of Animal Reproduction, 2024)
A dystociac ewe presented with the history of continuous straining, off feed and vaginal discharge was diagnosed with fetal monster- monocephalus tetrabrachius tetrapus and managed by cesarean operation.